No association between glutathione S-transferase M1 and T1 gene polymorphisms and susceptibility to endometriosis - Letícia C. Batista; Mariangela T. Ruiz-Cintra; Marco Fábio P. Lima; Alessandra Bernadete Trovó de Marqui (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Endometriosis is a common gynecologic disorder influenced by genetic and environmental factors. The glutathione S-transferase family is associated with endometriosis because its main function is cellular detoxification, so the absence of those enzymes may be a factor for the development of the disorder. Objective: Investigate the relationship between polymorphisms of GSTM1 and GSTT1 genes and endometriosis, in order to gain a better understanding of the association between detoxification genes and the susceptibility to endometriosis. Material and methods: Case-control study in 132 women (49 with endometriosis and 83 of the control group). The genotype was determined using multiplex polymerase chain reaction (PCR), observed in 10% polyacrylamide gel electrophoresis stained with silver nitrate, and statistical analysis was performed. Results: There was not a significant difference between the GSTM1 and GSTT1 null genotype in the endometriosis group and the control group (p = 0.9956). The same result was observed with the combined genotype (p = 0.8129). Conclusion: In the present study, the GSTM1 and GSTT1 polymorphisms are not associated with a higher risk of endometriosis.